The Doctrine of Frustration and Force Majeure in the Face of Covid 19: Effects in Contracts of International Carriage - Oladele, Okunowo; Danor, Jerry; Alake, A. A. (ABUAD Law Journal, 2023)
Generally, parties to a contract are bound by the terms and conditions of the contract. However, the obligation on a contracting party to fulfill its part of the contract is subject to unforeseeable events that may render the contract incapable of performance. These unforeseeable events can operate to bring the contract to an end, as it is regarded in law as the doctrine of frustration. However, parties can insert force majeure clause in the contract in order to define the scope of events that can discharge parties from performance of the contract. Contracts generally have been impacted by the outbreak of the Covid 19 pandemic as many contracts have been impossible of performance due to the restriction on movements and lockdown worldwide. The aviation industry is never the least affected as the Covid 19 pandemic prevented airlines from operating and fulfilling contracts of carriage of goods and passengers from one country to another even when contracts have been entered before the pandemic. This paper seeks to address the impact of Covid 19 on contracts generally, the position of the law on contracts impacted by frustrating events such as Covid 19 and with particular focus on aviation contracts. That is our recommendation that parties should insert force majeure clauses in their agreement in other to clearly define events that would operate to frustrate the contract and for ease of interpretation.